Acoustically propelled winged macroparticles - Enriquez Florat, Adriana; Sack, Achim; D'Angelo, Olfa (Journal of Applied Physics, 2024)
Self-propelled particles harvest and harness energy from their environment, transforming it into a controlled force that propels their motion. We present a mechanism to propel active macroparticles using low frequency noise (10-200 Hz). Thin polymer plates (wings) are acoustically excited at their second natural frequency; the mass of air displaced generates a counter-force, which propels the macroparticles. We show that the magnitude and direction of the propelling force can be tweaked through the wing’s shape, dimensions, and orientation. Finally, we design a macroparticle with bidirectional rotation: its rotation direction can be inverted by changing the frequency at which it is excited.
CRIS-Team Scopus Importer:2024-11-29

Advancing Solar Sintering for Building A Base On The Moon - Imhof, Barbara; Urbina, Diego; Weiss, Peter; Sperl, Matthias; Hoheneder, Waltraut; Waclavicek, René; Madakashira, Hemanth Kumar; Salini, Joseph; Govindaraj, Shashank; Gancet, Jeremi; Mohamed, Makthoum Peer; Gobert, Thibaud; et al. (69th International Astronautical Congress (IAC), 2017)
In the last few years, different concepts have been investigated in the context of building humantended bases in extra-terrestrial environments through ISRU. NASA has conducted a 3D printed habitat challenge in 2015, which put international focus on the topic. Amongst microwave sintering, contour crafting and other Additive Manufacturing (AM) technologies using local resources on extra-terrestrial bodies, solar sintering has been the least investigated. In this context, the project RegoLight, sintering lunar regolith with solar light, is currently being developed.. The project has been funded through the European Commission to advance the Technology Readiness Level (TRL) from 3 to 5 and comprises five partners. Under the lead of the DLR in Cologne, Space Applications Services (Belgium), COMEX (France), LIQUIFER Systems Group (Austria) and Bollinger + Grohmann Ingenieure (Austria) collaborate to advance solar sintering technology in preparation of infrastructure construction on the moon. The project started in November 2016 and will terminate end of April 2018. This paper provides an overview of project RegoLight with regard to the projects’ main objectives: − Utilization of the AM approach for automated fabrication of building elements. A regolith simulant feeder is used in a solar furnace, under ambient conditions. − Automated fabrication of larger structures through a mobile printing head outside the solar furnace and in ambient conditions − Demonstration of producing a ‘building element’ block from lunar regolith simulant by applying the solar sintering AM approach, using a solar furnace automated setup, under vacuum conditions. 69 International Astronautical Congress (IAC), Adelaide, Australia, 25-29 September 2017. Copyright ©2017 by the International Astronautical Federation (IAF). All rights reserved. IAC-17, C2.9.13 Page 2 of 17 − Production of a ‘building element’ with a fine structure (resolution ≤ 1.4 cm) from lunar regolith simulant without bonding agent, using a solar light source under ambient conditions. − Design and validation of an interlocking building element, which when combined could be used for a variety of space architecture and mission requirements in a modular fashion − Characterization of the building elements produced (materials metrology) − Study the application of solar sintering element manufacturing in the frame of the larger picture of a lunar base architecture; also by considering concepts such as the ESA “Moon Village” The ultimate goal of the project is to help pave the way for future long duration, sustainable, crewed exploration to the moon. Projects such as RegoLight use local resources to create ecological solutions using only lunar sand and the sun to build protective shelters for humans.<br

A gravity-independent powder-based additive manufacturing process tailored for space applications - Lopez-D'Angelo, Olfa; Kuthe, Felix; Liu, Szu-Jia; Wiedey, Raphael; Bennett, Joe M.; Meisnar, Martina; Barnes, Andrew; Kranz, W. Till; Voigtmann, Thomas; Meyer, Andreas (Additive Manufacturing, 2021)
The future of space exploration missions will rely on technologies increasing their endurance and self-sufficiency, including manufacturing objects on-demand. We propose a process for handling and additively manufacturing powders that functions independently of the gravitational environment and with no restriction on feedstock powder flowability. Based on a specific sequence of boundary loads applied to the granular packing, powder is transported to the printing zone, homogenized and put under compression to increase the density of the final part. The powder deposition process is validated by simulations that show the homogeneity and density of deposition to be insensitive to gravity and cohesion forces within a discrete element method (DEM) model. We further provide an experimental proof of concept of the process by successfully 3D printing parts on-ground and on parabolic flight in weightlessness. Powders exhibiting high and low flowability are used as model feedstock material to demonstrate the versatility of the process, opening the way for additive manufacturing of recycled material.<br
Keywords: Additive manufacturing; 3D printing; Powder handling; Powder-bed fusion; Discrete Element Method (DEM) simulation; Space technology; Weightlessness

All-terrain granular gripper - Santarossa, Angel; D'Angelo, Olfa; Sack, Achim; Pöschel, Thorsten (Particuology, 2025)
Granular grippers can manipulate a wide variety of objects, but need to be pressed against the object to conform to it. If the object is placed on unstable ground, e.g., on sand or water, this step might cause the object to sink or move away from the gripper, hindering proper operation. We introduce a granular gripper with an integrated suction cup, where suction and jamming are controlled independently. We demonstrate the system's robust and enhanced gripping capabilities by comparing its grasping performance with a typical granular gripper design. We show that the proposed device can grip objects that are challenging for typical granular grippers, including those placed on unstable ground, as the suction cup stabilizes the object, allowing the gripper to conform.
CRIS-Team Scopus Importer:2025-08-01
Keywords: All-terrain; Granular; Granular gripper; Jamming; Soft robotics; Suction

Curvature of gastrocnemius muscle fascicles as function of muscle-tendon complex length and contraction in humans - Heieis, Jule; Böcker, Jonas; D'Angelo, Olfa; Mittag, Uwe; Albracht, Kirsten; Schönau, Eckhard; Meyer, Andreas; Voigtmann, Thomas; Rittweger, Jörn (Physiological Reports, 2023)
It has been shown that muscle fascicle curvature increases with increasing contraction level and decreasing muscle-tendon complex length. The analyses were done with limited examination windows concerning contraction level, muscle-tendon complex length, and/or intramuscular position of ultrasound imaging. With this study we aimed to investigate the correlation between fascicle arching and contraction, muscle-tendon complex length and their associated architectural parameters in gastrocnemius muscles to develop hypotheses concerning the fundamental mechanism of fascicle curving. Twelve participants were tested in five different positions (90°/105°*, 90°/90°*, 135°/90°*, 170°/90°*, and 170°/75°*; *knee/ankle angle). They performed isometric contractions at four different contraction levels (5%, 25%, 50%, and 75% of maximum voluntary contraction) in each position. Panoramic ultrasound images of gastrocnemius muscles were collected at rest and during constant contraction. Aponeuroses and fascicles were tracked in all ultrasound images and the parameters fascicle curvature, muscle-tendon complex strain, contraction level, pennation angle, fascicle length, fascicle strain, intramuscular position, sex and age group were analyzed by linear mixed effect models. Mean fascicle curvature of the medial gastrocnemius increased with contraction level (+5 m-1 from 0% to 100%; p = 0.006). Muscle-tendon complex length had no significant impact on mean fascicle curvature. Mean pennation angle (2.2 m-1 per 10°; p < 0.001), inverse mean fascicle length (20 m-1 per cm-1 ; p = 0.003), and mean fascicle strain (-0.07 m-1 per +10%; p = 0.004) correlated with mean fascicle curvature. Evidence has also been found for intermuscular, intramuscular, and sex-specific intramuscular differences of fascicle curving. Pennation angle and the inverse fascicle length show the highest predictive capacities for fascicle curving. Due to the strong correlations between pennation angle and fascicle curvature and the intramuscular pattern of curving we suggest for future studies to examine correlations between fascicle curvature and intramuscular fluid pressure.
Created from Fastlane, Scopus look-up
Keywords: biomechanics; connective tissue; physiology; ultrasound

DEM9 Book of Abstracts - Angelidakis, Vasileios; D'Angelo, Olfa; Müller, Patric; Pöschel, Thorsten; Roy, Sudeshna; Xiao, Hongyi (2023)
DEM9 addressed the latest advancements in the simulation of particulate systems using discrete element methods, including coupled simulations, particle fragmentation, non-spherical particles, multiscale and multiphase systems.<br

Effect of particle size on the suction mechanism in granular grippers - Santarossa, Angel; D'Angelo, Olfa; Sack, Achim; Pöschel, Thorsten (Granular Matter, 2023)
Abstract: Granular grippers are highly adaptable end-effectors that exploit the reversible jamming transition of granular materials to hold and manipulate objects. Their holding force comes from the combination of three mechanisms: frictional forces, geometrical constraints, and suction effects. In this work, we experimentally study the effect of particle size on the suction mechanism. Through X-ray computed tomography, we show that small particles (average diameter d≈120μm) achieve higher conformation around the object than larger particles (d≈4mm), thus allowing the formation of air-tight seals. When the gripper is pulled off, mimicking lifting of an object, vacuum pressure is generated in the sealed cavity at the interface gripper–object. If the particles used as filling material are too large, the gripper does not conform closely around the object, leaving gaps between the gripper’s membrane and the object. These gaps prevent the formation of sealed vacuum cavities between the object and the gripper and in turn hinder the suction mechanism from operating. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-02-03
Keywords: Computed tomography; Granular gripper; Jamming transition; Soft robotics; Suction

Granularer Greifer - Pöschel, Thorsten; D'Angelo, Olfa; Pucheanu, Walter; Sack, Achim; Santarossa, Angel (2022)
Die Erfindung betrifft einen granu- laren Greifer (1), insbesondere für einen Roboterarm, aufweisend einen Träger (2), eine an dem Träger (2) befestigte Membran (4), die ballonartig einen Innenraum (6) umschließt, ein in den Innenraum (6) eingefülltes Granulat (10), und einen ersten Fluidanschluss (12), der in den Innenraum (6) führt und im bestimmungsgemäßen Betrieb zum Fördern von Fluid aus dem oder in den Innenraum (6) dient. Außerdem weist der Greifer (1) einen glockenartigen Einsatz (14) auf, der in dem Innenraum (6) angeordnet und in einem im bestimmungsgemäßen Betrieb des granularen Greifers (1) einem zu greifenden Objekt zugewandten Bereich mit einem ringartig geschlossenen Rand (20) innen- seitig auf die Membran (4) aufgesetzt ist, und einen zweiten Fluidanschluss (16), der in den Innenraum (6) führt, mit dem Einsatz (14) fluidführungstechnisch verbunden ist und im bestimmungsgemäßen Betrieb zum Fördern von Fluid aus einem oder in einen Zwischenraum (22) zwischen dem Einsatz (14) und der Membran (4) dient.
Keywords: Robotik; Greifer; Jamming in granularen Stoffen

Granular piston-probing in microgravity: powder compression, from densification to jamming - Lopez-D'Angelo, Olfa; Horb, Anabelle; Cowley, Aidan; Sperl, Matthias; Kranz, W. Till (npj microgravity, 2022)

Powder-based Additive Manufacturing for Space - Lopez-D'Angelo, Olfa (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
As human reach into space expands, need arises for versatile technologies, working under extreme conditions – notably, in absence of gravity. In-Space Manufacturing (ISM) would allow payload optimisation by enabling on-demand production of tools, spare parts or building elements, increasing self-sufficiency of long-endurance missions. While powder-based three dimensional (3D) printing processes offer high printing quality and adaptability to multiple raw materials, for all techniques available today, constrains remain on feedstock flow properties and recyclability of base-material. The work presented here proposes a new method for handling and additively manufacturing granular materials, independently of the gravitational environment, and emancipating from requirements on powder-feedstock flow properties. Technical evolutions go hand in hand with an understanding of the physical phenomena that underlie them. The development of a powder-based Additive Manufacturing (AM) process was hence preceded by a study of the factors influencing granular rheological response. To be used as demonstrator, a spherical polystyrene (PS) powder was modified to increase its surface roughness, resulting in two powders similar in all respects but their surface state. The link between physical and rheological properties of powders was explored, through typical rheometry tests (flow start-up and stationary flow curves, powder-bed tensile strength), but also through phenomenological testing methods found in industrial applications (notably the flow energy test). Observing and quantifying essential differences in flow-behaviour emerging from this modification of the frictional interactions between particles, allowed to approach the ill-defined concept of powder flowability, to propose a definition which encompasses not only the inherent powder physical properties, but also the environmental factors surrounding the material. To query the influence of such environmental factors, the same powder was used to study the effect of gravity (and absence thereof) on piston-probing of granular material. Using parabolic flight as a microgravity platform, this experiment revealed that, in absence of the secondary force field provided by gravity, powder flow deteriorates and packing fraction at jamming lowers, with dramatic consequences for powder handling in reduced gravity. Results from this first experimental campaign led to the design of the mentioned AM process. To deposit the granular base-material, this process uses solely driving mechanisms in- dependent of gravity (namely shear and shaking). To allow versatility in feedstock material’s flow-behaviour, adaptability of the process printing parameters was implemented through a control loop fed by in-situ probing during powder handling. The material deposition method was first validated through Discrete Element Method (DEM) simulation, showing no dependence of the process efficiency on the gravitational environment, nor on the increased interparticle cohesive forces. Experimental demonstration was also provided, through the construction of two prototype 3D printers, used on-ground and on parabolic flights to manufacture parts from the two powders mentioned above: PS powders of high and mediocre flowability. The successful manufacturing of parts under gravity as well as in weightlessness, from both powders, regardless of their flow properties, represents the main achievement of this work. X-ray computed tomography (CT) analysis of the sintered parts showed no systematic change in porosity between the samples manufactured under different gravitational environments, with near-perfect density and isotropic porosities. Parts were also produced directly from recycled material (under 1g), obtained by closed-loop recycling of former 3D printed parts; an achievement that no commercially available additive manufacturing process to date could realise, and that will be a critical asset for increasing the self-sustainability of space exploration missions. The work presented lead to filing a patent in September 2020, endorsed by the German Aerospace Center, under the application number 10 2020 123 753.7 for an “Apparatus and Method for Additive Manufacturing of Components in Environments with Various Gravitation- levels and with Materials of Different Flowability”.<br

Spreading of droplets under various gravitational accelerations - D'Angelo, Olfa; Kuthe, Felix; Van Nieuwland, Kasper; Janssen, Clint Ederveen; Voigtmann, Thomas; Jalaal, Maziyar (Review of Scientific Instruments, 2022)
We describe a setup to perform systematic studies on the spreading of droplets of complex fluids under microgravity conditions. Tweaking the gravitational acceleration under which droplets are deposited provides access to different regimes of the spreading dynamics, as quantified through the Bond number. In particular, microgravity allows us to form large droplets while remaining in the regime where surface tension effects and internal driving stresses are predominant over hydrostatic forces. The vip-drop(2) (visco-plastic droplets on the drop tower) experimental module provides a versatile platform to study a wide range of complex fluids through the deposition of axisymmetric droplets. The module offers the possibility to deposit droplets on a precursor layer, which can be composed of the same or a different fluid. Furthermore, it allows us to deposit four droplets simultaneously while conducting shadowgraphy on all of them and observing either the flow field (through particle image velocimetry) or the stress distribution inside the droplet in the case of stress birefringent fluids. It was developed for a drop tower catapult system, is designed to withstand a vertical acceleration of up to 30 times the Earth's gravitational acceleration in the downward direction, and is capable of operating remotely under microgravity conditions. We provide a detailed description of the module and an exemplary data analysis for droplets spreading on-ground and in microgravity. (C) 2022 Author(s).
CRIS-Team WoS Importer:2022-11-25

Spreading of droplets under various gravitational accelerations: the VIP-DROP2 module - Lopez-D'Angelo, Olfa; Kuthe, Felix; van Nieuwland, Kasper; Ederveen Janssen, Clint; Voigtmann, Thomas; Jalaal, Mazyiar (Review of Scientific Instruments, 2022)

Structural features of jammed-granulate metamaterials - Götz, Holger; Pöschel, Thorsten; D'Angelo, Olfa (Physical Review Research, 2024)
Granular media near jamming exhibit fascinating properties, which can be harnessed to create jammed-granulate metamaterials: materials whose characteristics arise not only from the shape and material properties of the particles at the microscale but also from the geometric features of the packing. For the case of a bending beam made from jammed-granulate metamaterial, we study the impact of the particles' properties on the metamaterial's macroscopic mechanical characteristics. We find that the metamaterial's stiffness emerges from its volume fraction, in turn originating from its creation protocol; its ultimate strength corresponds to yielding of the force network. In contrast to many traditional materials, we find that macroscopic deformation occurs mostly through affine motion within the packing, aided by stress relief through local plastic events, surprisingly homogeneously spread and persistent throughout bending.
CRIS-Team Scopus Importer:2024-02-02

Understanding dense granular flow from first principles - Kranz, W. Till; Coquand, Olivier; Lopez-D'Angelo, Olfa (Science Talks, 2022)
Preventing natural disasters like avalanches or landsides, optimising powder-based industrial processes or predicting the flow of sand on planetary surface, are exemplary applications that would benefit from a universal model for a better understanding of granular rheology. Due to the high densities and shear rates involved, the derivation of constitutive equations from first principles is notoriously difficult. Here, we will present such a theoretical approach, the Granular Integration Through Transients (GITT) formalism. Starting from the microscopic equations of motion, GITT yields quantitative predictions for the flow curves of granular fluids at high density and shear rate. GITT predicts Newtonian, shear thinning, and shear thickening regimes depending on density and shear rate. We will present experiments in a fluidized bed rheometer that confirm the rheological regimes and can be evaluated quantitatively in terms of GITT. We will discuss a phenomenological version of GITT that makes the qualitative behaviour understandable in terms of dimensionless numbers. With this we can derive the mu(I)-rheology that has been proposed as an empirical law for granular flow and show that it is a special case of GITT for specific flow conditions.<br